2016
DOI: 10.4103/0972-0707.186451
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonic versus sonic activation of the final irrigant in root canals instrumented with rotary/reciprocating files: An in-vitro scanning electron microscopy analysis

Abstract: Aim:To compare the smear layer and debris removal in root canals instrumented with two different kinematic motions after ultrasonic and sonic irrigation activation.Materials and Methods:Eighty freshly extracted teeth were selected for the study and randomly divided the samples into two groups (n = 40) for instrumentation with either rotary ProTaper NEXT (PTN) or reciprocating WaveOne (WO) file systems. These (n = 40) were further divided into two groups (n = 20) where the final irrigant was activated using eit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 25 publications
1
20
0
Order By: Relevance
“…The treatments conducted have shown that PUI and the EA system produce comparable smear layer removal results when used with rotary instrumentation [ 10 , 11 ]. To our knowledge, however, few studies have been conducted to compare both irrigation protocols in this respect, after single-file reciprocating instrumentation [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…The treatments conducted have shown that PUI and the EA system produce comparable smear layer removal results when used with rotary instrumentation [ 10 , 11 ]. To our knowledge, however, few studies have been conducted to compare both irrigation protocols in this respect, after single-file reciprocating instrumentation [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…But in sonic system, no influence by lateral wall contact is seen. 19 In this study, it was seen that EndoActivator has more efficacy in removing smear layer than syringe irrigation. On the contrary a study done by Uroz-Torres et al 20 showed that there was no difference between Endoactivator and syringe irrigation in smear layer removal.…”
Section: Discussionmentioning
confidence: 69%
“…While in other study carried out by Khalap et al 19 it was concluded that sonic activation is better than ultrasonic activation in debris removal. The reason given was that PUI creates acoustic microstreaming producing enough shear stresses that disrupts debris from prepared canals.…”
Section: Discussionmentioning
confidence: 85%
“…To improve bacterial eradication, irrigants must be in close approximation to the root canal. The standard needle irrigation technique pushes the irrigant for a maximum of 1.1 mm beyond the needle tip (Khalap et al, 2016). Although sodium hypochlorite can infiltrate dentinal tubules, the extent of its penetration is affected by time, temperature, and concentration (Zou et al, 2010).…”
Section: Discussionmentioning
confidence: 99%